2020
DOI: 10.1007/978-3-030-43520-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Hardness of Network Satisfaction for Relation Algebras with Normal Representations

Abstract: Robin Hirsch posed in 1996 the Really Big Complexity Problem: classify the computational complexity of the network satisfaction problem for all finite relation algebras A. We provide a complete classification for the case that A is symmetric and has a flexible atom; the problem is in this case NP-complete or in P. If a finite integral relation algebra has a flexible atom, then it has a normal representation B. We can then study the computational complexity of the network satisfaction problem of A using the uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Example 6.8 (Hardness of representable relation algebra #17, see Bodirsky & Knäuer, 2020). Let N be the normal representation of the algebra #17 mentioned in Example 3.9.…”
Section: Binary Injective Polymorphismsmentioning
confidence: 99%
“…Example 6.8 (Hardness of representable relation algebra #17, see Bodirsky & Knäuer, 2020). Let N be the normal representation of the algebra #17 mentioned in Example 3.9.…”
Section: Binary Injective Polymorphismsmentioning
confidence: 99%
“…The following shows how to apply our hardness result to a concrete A ∈ RRA. Example 37 (Hardness of relation algebra #17, see Bodirsky and Knäuer 2020a)).…”
Section: Np-hardnessmentioning
confidence: 99%
“…Moreover, Hirsch [42] proposed studying the computational complexity of CSPs for relation algebras, with obvious applications in AI. Inspired by this research programme, Bodirsky and Knäuer [19] recently identified sufficient conditions for homogeneity of relation algebras. Their results provide further examples of CSPs that are covered by Theorem 6.…”
Section: Proposition 19 Every Problem In T Is Fpt Parameterized By Th...mentioning
confidence: 99%